High functioning ASD profile adult employees in global labour markets. ICT supported employment. - Koutsonika, Helen; Drigas, Athanasios (Technium Sustainability, 2022)
The present study critically examines the issue of the HF-ASD adult employees’ working life shedding light on some of its aspects (e.g., internal developmental difficulties, employment status of neglected candidates, very special characteristics-promoters to meaningful employment) as well as the support provided to the specific population, especially by means of ICT, so as they could overcome obstacles in the job market and manage their career routes.